2022
DOI: 10.1021/acs.langmuir.2c02032
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide-Derived Ice Recrystallization Inhibitors with a Modular Design: The Case of Dextran-Based Graft Polymers

Abstract: Ice recrystallization inhibitors inspired from antifreeze proteins (AFPs) are receiving increasing interest for cryobiology and other extreme environment applications. Here, we present a modular strategy to develop polysaccharide-derived biomimetics, and detailed studies were performed in the case of dextran. Poly­(vinyl alcohol) (PVA) which has been termed as one of the most potent biomimetics of AFPs was grafted onto dextran via thiol–ene click chemistry (Dex-g-PVA). This demonstrated that Dex-g-PVA is effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…Poly­(vinyl alcohol) (PVA) exhibits very high IRI activity and is often used as a positive standard for IRI activity. The molecular weight, degree of deacetylation, and tacticity of PVA affect the IRI activity. , Grafted PVAs to hyaluronic acid, pectin, and alginate maintain the IRI activity . Poly­(Fulvo-co-Oxo), a facially amphipathic polymer, exhibits high IRI activity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly­(vinyl alcohol) (PVA) exhibits very high IRI activity and is often used as a positive standard for IRI activity. The molecular weight, degree of deacetylation, and tacticity of PVA affect the IRI activity. , Grafted PVAs to hyaluronic acid, pectin, and alginate maintain the IRI activity . Poly­(Fulvo-co-Oxo), a facially amphipathic polymer, exhibits high IRI activity .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Grafted PVAs to hyaluronic acid, pectin, and alginate maintain the IRI activity. 15 Poly(Fulvo-co-Oxo), a facially amphipathic polymer, exhibits high IRI activity. 16 Recently, poly(Ala-co-Lys) was reported to exhibit very high IRI activity, comparable to that of PVA.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In previous studies, we have identified some novel antifreeze agents and discussed corresponding mechanism. Herein, we choose histidine and phenylalanine as two model molecules to investigate their IRI activity through experiment and molecular dynamics (MD) simulation. Both are α-amino acids containing an alanine moiety and one aromatic ring.…”
Section: Introductionmentioning
confidence: 99%
“…The scaled-up production of AFPs with a reasonable cost is still difficult. Synthetic polymers have been widely developed as AFP biomimetics, such as poly(vinyl alcohol) (PVA), poly(ethylene glycol) (PEG), and their block copolymers. , Besides, pronounced IRI activities have also been seen on graphene oxide (GO), nanocelluloses with amphiphilic structures, and facially amphipathic glycopolymers synthesized by ring-opening metathesis polymerization, analogous to natural antifreezing glycoprotein such as poly([( l -Ala) x - co -( l -Thr succinate) y , nanogels, high molecular weight polyproline, oligonucleotides, and surface-functionalized MOF particles . Since synthetic materials are less active than natural AFPs, researchers are turning their focus to the higher-ordered nanostructures .…”
mentioning
confidence: 99%